1 - Why Measurement Matters: The Learning Outcomes Approach – A Case Study from Canada - MacFarlane, Alexandra; Brumwell, Sarah (Journal of Higher Education in Africa, 2022)
Learning outcomes assessment can be a valuable tool for improving educational quality and institutional accountability. When learning outcomes, learning experiences and assessment tasks are aligned, the learning outcomes approach can ground quality assurance and teaching, and learning improvements in direct evidence of student learning. We offer our experiences as an informal case study on the use and development of learning outcomes assessment for quality assurance purposes. Since assessment is the keystone of the learning outcomes approach, our reflections are more broadly driven by the question of how best to measure and demonstrate student learning. This question takes on challenging new dimensions when we consider the fact that the evidence collected through the assessment of learning outcomes must be sound enough to support multiple policy goals.